Wideband measurement of transistor small signal parameters by time domain spectrometry - Young, G. M. (College of Aeronautics, 1969)
Time Domain Spectrometry (TDS) Methods are outlined and their application to measurement of transistor parameters is discussed. Experimental results are presented and the advantages and limitations of TDS methods are re-assessed. Future developments are suggested.